Recent Fall in the SDR Interest Rate : Implications and Proposed Amendments to Rule T-1. (Policy Papers; Policy Paper, 2014)
The SDR interest rate is at historic lows. Under the current Rule T-1, the SDR interest rate is calculated as the weighted average of interest rate instruments in the SDR basket, and stood at just 3 basis points for the week of October 13th. Market rates could decline further, which could reduce the SDR interest rate to zero or negative levels under the formula of the current Rule T-1. However, there is no authority under the Articles of Agreement for the Fund to establish a zero or negative SDR interest rate. The wording of the relevant provisions in the Articles does not leave room for a zero or negative rate, and nothing in the legislative history of the First and Second Amendments suggests that zero or negative rates were ever contemplated. Negative SDR interest rates would also have adverse implications for the Fund's finances. Moreover, very low SDR interest rates affect the functioning of the burden sharing mechanism for deferred charges. Under current Board decisions, the equal burden sharing, where creditors and debtors as a group generate equal amounts to cover deferred charges, requires a minimum positive SDR interest rate to operate. The SDR interest rate has now fallen below that minimum level. This paper proposes technical amendments to Rule T-1 and the burden sharing mechanism to address these issues. In particular, the paper proposes setting a 5 basis point floor on the SDR interest rate, changing the rounding rules on the SDR interest rate and the burden sharing adjustment, and reducing the 1 basis point minimum of the burden sharing adjustment to 0.1 basis point. These measures would preserve a minimal capacity of equal burden sharing aimed at protecting the Fund's balance sheet, while limiting potential departures of the SDR interest rate from market interest rates.